Land Use and Water Quality - Kronvang, Brian; Fraters, Dico; Wendland, Frank (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This collection of 11 papers introduces broad topics covering various professional disciplines related to the research arena of land use and water quality. The papers exemplify the important links between agriculture and water quality in surface and ground waters as well as the pollution problems around urban areas. Advancement of new technologies for analyzing links between land use and water quality problems as well as insights into new tools for analyzing large monitoring datasets are highlighted in this collection of papers.